Estimation of efficiency of functioning of enterprises in the production of building materials of Ivano-Frankivsk region - Андрусів, У. Я. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the article the estimation of efficiency of functioning ofenterprises of sphere of producti on of building materials isconducted after resource, having a special purpose andstructural efficiency on t he basis of determination oftaxonomical integral index of estimation of efficiency offunctioning of enterp rise. Offered approach to the estimationof efficiency of structural changes of enterprise after thecoefficien t of firmness of the economy growing. After theworked out scales and set levels of values of indexes amat rix is built a "integral index of estimation of efficiency offunctioning of enterprise is a coefficient of firmn ess of theeconomy growing" and positioning in her of enterprises ofsphere of production of building mate rials of Ivano-Frankivsk area.